Mimosa scabrella Benth seedling growth in different recipients size and fertilizers doses function - Stüpp, Ângela Maria; Navroski, Marcio Carlos; Felippe, Dionéia; Kniess, Daniella Del Castanhel; Amancio, Julio Cesar; Silva, Matheos Abner; Pereira, Mariane de Oliveira (Revista Ecologia e Nutrição Florestal - ENFLO, 2015)
This study evaluated different sized tubes and controlled release fertilizer doses to produce Mimosa scabrella seedlings. Tubes of 110 cm³ and 180 cm³ were used, filled with commercial substrate Tecnomax® and added 0, 3, 6 and 9 g L-1 Osmocote®. The experiment was conducted in a completely randomized design, in a factorial 2 x 4. We used four replicates, each consisting of 16 plants. Evaluations were made 96 days after sowing. Morphologic analysis was performed by means of shoot height measurements (cm), stem diameter (mm) and the ratio of shoot height and diameter (H/D). The dosage of fertilizer that is more efficient was 6 g L-1, and the cartridge that had the most satisfactory result was 180 cm³. The slow-release fertilizer levels influenced the early growth of seedlings Mimosa scabrella, showing potential use in the fertilization of the specie.